Meditation Guidance, Spiritual Strengthening, and Mental Health for Patients with Covid-19: Neuroscience Approach - Mohammad Jailani; Suyadi Suyadi (Universitas Ahmad Dahlan, 2023)
Background: The spread of the Covid-19 virus outbreak in early March 2020, caused a high number of deaths worldwide. People infected with Covid-19 are not only physically infected but mentally (spiritually) are also infected. In Indonesia, many hospitals in all cities and villages have been instructed to lock down (limit communication and interaction). This research focuses on analyzing neuro-spiritual as an alternative spiritual approach to improving mental health for Covid-19 patients. Method: This study uses a qualitative method (content analysis), based on case studies at Muhammadiyah hospitals throughout the city of Yogyakarta, Indonesia which are fully accredited (perfect). This study interviewed asymptomatic and symptomatic Covid-19 patients using a purposive sampling technique. The data qualitative analysis technique uses triangulation. Results: This study describes that patients suffering from Covid-19 are very diverse. Before the neuro-spiritual approach, Covid-19 patients felt constrained. The existence of a neuro-spiritual approach, namely a spiritual approach, such as fasting, night prayers (tahajjud), reading the Koran, and interacting with friends, has a good and positive impact on Covid-19 patients. A neuro-spiritual approach that prioritizes and relies on spiritual power (worship) that responds to the brain, is an alternative method used by PKU Muhammadiyah Yogyakarta. Conclusion: A neuro-spiritual approach can improve the mental health of Covid-19 patients. This approach is very relevant to the reference perspective of Islamic studies which has implications for the Covid-19 disaster in Indonesia.